ENGLISH STUDENTS’ EXPERIENCE OF MONOLOGUE PRACTICE IN RELATION TO SPEAKING FLUENCY AT STKIP BINA MUTIARA - Diennur, Usman; Setiawan Muhammad, Aris; Amelia, Riska; Julyanti, Mutia; Riskawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to explore students’ experiences in monologue practice and its relation to speaking fluency. This study used a descriptive qualitative method with a phenomenological approach. The participants of this study were 10 students of STKIP Bina Mutiara who had experience in monologue practice. Data were collected through interviews, observations and documentation. The findings showed that students experienced various cognitive, affective, behavioral and reflective experiences during monologue practice. Cognitive experiences included difficulties in remembering vocabulary, constructing sentences and thinking directly in English. Affective experiences included feelings of nervousness, anxiety, comfort and confidence during monologue activities. Behavioral experiences included the use of fillers, pauses, repetition and losing track of ideas while speaking. Reflective experiences showed that students became more aware of the development of their vocabulary, pronunciation, speaking ability, learning process and confidence. The findings also showed a relation between monologue practice and speaking fluency, which was reflected in improved speech flow, reduced hesitation and pauses and more spontaneous speaking. Overall, this study showed that monologue practice provided meaningful speaking experiences and supported the development of students’ speaking fluency.